Review of the Results of WT1 Peptide Vaccination Strategies for Myelodysplastic Syndromes and Acute Myeloid Leukemia from Nine Different Studies - Di Stasi, Antonio; Jimenez, Antonio M.; Minagawa, Kentaro; Al-Obaidi, Mustafa; Rezvani, Katayoun (Frontiers in Immunology, 2015)
We performed a systematic review of data from seven clinical trials of WT1 peptide vaccination in patients with myelodysplastic syndromes and/or acute myeloid leukemia (MDS/AML), published between 2004 and 2012. A total of fifty-one patients were eligible for analysis. Vaccination with WT1 peptides proved safe and feasible in patients with MDS/AML, in studies from different institutions. Additionally, clinical responses and clinical benefit were observed, with some patients achieving and maintaining remission long term (more than 8 years). A significant correlation between induction of WT1 specific T cells and normalization/reduction of WT1 mRNA levels and progression free survival was noted in a number of studies. However larger studies are warranted to confirm these results. Interestingly, the majority of trials reported the presence of WT1 specific T cells with limited or absent functionality prior to vaccination, which increased in frequency and function after vaccination. In conclusion, WT1 peptide vaccination strategies were safe in this heterogeneous group of patient with MDS/AML. Larger and more homogeneous studies or randomized clinical trials are needed to quantify the contribution of WT1 peptide vaccines to clinical responses and long term survival.